Mengidentifikasi Miskonsepsi Logaritma Siswa SMA Kelas X - Anzar; Muhammad Darwis M; Asdar (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2017)
This study aims to identify misconceptions on logarithm of students at class X. This research is categorized as descriptive research with quantitative approach. Subjects in this study were students of class X, selected with purposive sampling technique. Data were collected by diagnostic test method. Instrument in this study is multiple choice test with four choices of answers. Students are also required to fill in the CRI score as a student's level of confidence in the chosen answer. Students’ understanding categories are obtained from combination of diagnostic test results (true or false) with CRI values (high or low). The results of this study indicate that the highest category of conceptual understanding of the logarithmic material of students at Class X senior high school is the misconception category. Students' misconceptions on logarithmic material still occur in each indicator. The percentage of students who experience the highest misconceptions at indicators that discuss understanding the values of various logarithmic forms and able to sort the logarithmic numbers from the smallest number to the largest number. The lowest misconception occurs at indicators that discuss using logarithmic properties in solving simple logarithmic equations.